Comparison of two continuous non-invasive haemodynamic monitoring techniques in the perioperative setting - Jackevičiūtė, Jonė; Kraujalytė, Greta; Jaremko, Inna; Stremaitytė, Vilija; Gudaitytė, Jūratė (Acta medica Lituanica, 2019)
Background. The aim of the study was to identify the accuracy of and agreement between two non-invasive haemodynamic monitoring techniques in the perioperative setting – thoracic electrical bioimpedance (TEB) and Edwards Lifesciences ClearSight system (CS). Materials and methods. The study included ten patients. Parametric quantitative data were expressed as mean ± SD. The ShapiroWilk test was used to test the normality of the distributions. A linear regression model was used to measure the strength of the linear relationship between TEB and CS. Bland-Altman analysis was performed to assess the mean difference, precision, and the limits of agreements (LOA). The Critchley and Critchley method was used to calculate the percentage error (PE), and if
Keywords: haemodynamic monitoring; cardiac output; non-invasive; intraoperative; pulse wave analysis; bioimpedance